When do relative prices matter for measuring income inequality? The case of food prices in Mozambique - Channing Arndt; Sam Jones; Vincenzo Salvucci (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Changes in relative prices of commodities consumed in different shares across income groups can be expected to alter real income differentials between these groups. Using Mozambican household budget survey and price data from 2002/03 and 2008/09, we show that once relative price increases are accounted for, inequality of real consumption increases substantially. We obtain this result by constructing a price deflator that reflects divergent price dynamics of different product categories. Since the main factors driving this result prevail in other developing countries, it is likely that inequality may be underestimated elsewhere.
Keywords: E31; D12; D31; O55; 330; relative price changes; price index; income inequality; Mozambique